Recent Progress in the Synthesis and Applications of Composite Photocatalysts: A Critical Review. Issue 2 (16th December 2021) - Humayun, Muhammad; Wang, Chundong; Luo, Wei
Abstract: Photocatalysis is an advanced technique that transforms solar energy into sustainable fuels and oxidizes pollutants via the aid of semiconductor photocatalysts. The main scientific and technological challenges for effective photocatalysis are the stability, robustness, and efficiency of semiconductor photocatalysts. For practical applications, researchers are trying to develop highly efficient and stable photocatalysts. Since the literature is highly scattered, it is urgent to write a critical review that summarizes the state‐of‐the‐art progress in the design of a variety of semiconductor composite photocatalysts for energy and environmental applications. Herein, a comprehensive review is presented that summarizes an overview, history, mechanism, advantages, and challenges of semiconductor photocatalysis. Further, the recent advancements in the design of heterostructure photocatalysts including alloy quantum dots based composites, carbon based composites including carbon nanotubes, carbon quantum dots, graphitic carbon nitride, and graphene, covalent–organic frameworks based composites, metal based composites including metal carbides, metal halide perovskites, metal nitrides, metal oxides, metal phosphides, and metal sulfides, metal–organic frameworks based composites, plasmonic materials based composites and single atom based composites for CO2 conversion, H2 evolution, and pollutants oxidation are discussed elaborately. Finally, perspectives for further improvement in the design of composite materials for efficient photocatalysis are provided. Abstract : In semiconductor photocatalysis, the fate of photogenerated charge carriers (electron–hole pairs) is decided by the relative conduction and valence band potentials of the photocatalysts and the redox levels of substrate. The employment of photocatalysts in photocatalysis is widely investigated. This review summarizes a broad overview of semiconductor composite photocatalysts for Sol Energy conversion and environmental remediation.